2006
DOI: 10.1079/joh2005314
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of routine inspection methods for porcine cysticercosis in Zambian village pigs

Abstract: The value of tongue and meat inspection as diagnostic tools for porcine cysticercosis was assessed in 65 Zambian village pigs by comparing the results with carcass dissections. In addition, the intensity of infections, distribution and viability of cysts in infected pigs were measured. Five pigs (7.7%) were positive on tongue examination, while routine meat inspection showed 12 (18.5%) positives. However, carcass dissections detected cysticerci in 31 (47.7%) pigs. The range in number of cysticerci was 1 to 14,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 9 publications
(18 reference statements)
6
59
0
Order By: Relevance
“…Detailed necropsy was then performed only on the experimentally infected pigs, from which the entire musculature and organs were cut into thin slices of about 0.5cm (Boa et al 2002). The cysticerci were classiϐied as vesicular and non-vesicular based on their macroscopic appearance (Phiri et al 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed necropsy was then performed only on the experimentally infected pigs, from which the entire musculature and organs were cut into thin slices of about 0.5cm (Boa et al 2002). The cysticerci were classiϐied as vesicular and non-vesicular based on their macroscopic appearance (Phiri et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Dorny et al (2004) describe a similar ϐinding and estimated the sensitivity of tongue examination and carcass inspection to be 21 and 22%, respectively. Phiri et al (2006) also found that pigs with a low parasite burden did not test positive through tongue examination and carcass inspection, as these methods failed to detect cysticercosis in 83% and 61% of the animals, respectively. In endemic areas, most commercialized pigs with light infection may escape from being detected by meat inspection and the consumption of undercooked pork meat is therefore a risk factor for infection.…”
Section: Detection Of Circulating Antigen Using Ag-elisamentioning
confidence: 99%
See 1 more Smart Citation
“…Viable cysticerci had well-limited thin-walled cystic structures containing clear vesicular fluid and a visible whitish protoscolex. Degenerated cysticerci were non-cystic but rather had semi-solid caseous masses with no discernible parasite structures (Phiri et al, 2006). This experiment was reviewed and approved by the Committee on Animal research of the School of Veterinary Medicine, UNMSM.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The thickness of the slices was <0.5 cm, ensuring exposure of fully developed cysts (Phiri et al, 2006). Cysticerci and cysticercus-like structures were sought in muscles and organs, and after removal stored in ethanol 70% for molecular identification of the Taenia species.…”
Section: Molecular Diagnosismentioning
confidence: 99%